L’amphithéâtre de Reims/Durocortorum : nouveaux éléments de localisation et de datation - Pierre Mathelart (Gallia)
The amphitheater represents one of the most emblematic urban buildings in Antiquity. During the Roman period, the ancient city of Reims/Durocortorum, having been elevated to the rank of provincial capital for Gallia Belgica, required construction of one such urban monument. Although the existence of this building in Reims is not mentioned in ancient literary sources, the study of later texts seems to indicate that it was located to the north, on the edge of the city, beyond the Porte de Mars, and that it was still in use in the 13th c. for military inspections. However, other, later sources also indicate that the building was almost completely destroyed in the 16th c. and that it disappeared entirely at the end of the modern era. Its memory was preserved with the bestowal of the toponym “Mont d’Araisne.” Several ancient plans either directly mention or allude to the presence of this amphitheater. In 2007-2008, the installation of a new tramway line presented the opportunity to excavate this area, specifically along the outskirts of the current Saint-Thomas church. This operation brought to light the presence of two curvilinear walls, almost entirely recovered at the end of Antiquity, and filled in between by a thick chalk backfill. These architectural remains are interpreted as constituting the wall of the ancient amphitheater, on the one hand, and an esplanade surrounded by a peribolos wall, on the other. Under this platform and within its vicinity, the remains of an earlier occupation are sufficiently well preserved to reconstruct its organization. These remains attest to the presence of palisaded plots of land whereon buildings with cellars were established. Abundant material goods were retrieved, primarily ceramics (2,757 fragments, minimum number of individuals [MNI]: 216), discarded in the fillings of the hollow structures at the time of the abandonment of these early settlements, prior to the construction of the performance building. The range of ceramics consists mainly of Italic or Gallic-type terra sigillata vessels, as well as Gallo-Belgian style objects. The analysis of this material allows us to propose a chronological connection and approximate date for the construction of the amphitheater. Firstly, this evaluation led to the association of this assemblage with other collections from the area. When examined together, they define and delineate the scope of the overview IV, in terms of the evolution of ancient tableware in Reims. Careful observation of the different proportions of the categories and types of ceramics in the corpus, as well as in other contemporary Reims reference contexts now allows us to subdivide this scope in two. The corpus of material goods from the levels corresponding to the abandonment of the structures and preceding the construction of the amphitheater is consistent with the most recent phase. If the three coins present alongside this material do not appear to indicate a date before the beginning of the 1st c. AD, the other coins associated with these levels allow us to propose a dating between 15-20 and 40-45 AD and, for the most recent phase, between 30 and 40-45 AD. Thus, according to the data collected from this excavation, the Reims amphitheater was most likely built during the second quarter of the 1st c., during Tiberius’ principate. Based on this proposal, the Reims amphitheater appears to have been built during the first construction phase of buildings dedicated to performance in the Roman Empire, concurrently, or shortly after the erection of the amphitheaters of Lyon (Rhône) and Saintes (Charente-Maritime), two other capitals of Gaul. Though knowledge about the amphitheater itself remains very limited, the location of and date of foundation for this emblematic monument of Roman culture in Reims now appear to have been identified thanks to this excavation.